Effect of machining parameters on surface roughness during wet and dry Wire-EDM of stainless steel - Abdulkareem, Suleiman; Khan, Ahsan Ali; Mohd Zain, Zakaria (Asian Network for Scientific Information, 2011)
Surface integrity of Machined parts is one of the major machining characteristics that play an important role in determining the quality of engineering components. It is well-known fact that good quality surfaces improve the fatigue strength, corrosion and wear resistance of workpiece. The purpose of this study was to investigate the effects of Wire-Electrical Discharge Machining (WEDM) variables on surface topography of stainless steel. In the present work, the effects of pulse current and gap voltage on surface topography during wet and dry WEDM of stainless steel were investigated. It was evident that as the two process parameters increase the surface topography of workpiece becomes worse. The effect of both dry and wet machining conditions on surface topography is also reported in this paper.